Funkcjonowanie controllingu w cementowni - Biadacz, Renata (The Functioning of Controlling in a Cement Factory., 2006)
Controlling plays an important role in cement factories as one of key management instruments. Controlling is implemented in those companies which try to effectively solve problems. The paper covers the following subjects: a) the role of controlling in a cement factory, b) the process of controlling implementation in a cement factory, c) the influence of controlling on effective management in a cement factory.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 73-80